Investment and Saving Relationship in South Asia - Ahmad, Shabbir (International Journal of Economics and Financial Issues, 2017)
This study tests the Feldstein and Horioka hypothesis (1980) for four South Asian developing economies and an oil producing economy, Saudi Arabia. Performing cointegration tests on annual data, the results indicate that approximately one to one long run relationship between investment and saving is present in India and Saudi Arabia thus validating the above hypothesis while a weak form relation for Bangladesh, Pakistan, and Sri Lanka shows the existence of Feldstein and Horioka puzzle. Keywords: Saving-investment, cointegration, South Asia JEL Classifications: C32; E21; F41